Diagnosis and Care of Infants and Children with Pompe Disease - Hahn, Andreas; Hennermann, Julia B.; Huemer, Martina; Kampmann, Christoph; Marquardt, Thorsten; Mengel, Eugen; Müller-Felber, Wolfgang; Muschol, NicoleMaria; Rohrbach, Marianne; Stehling, Florian (Klinische Pädiatrie, 2020)
Pompe disease is a rare metabolic myopathy caused by deficiency of lysosomal α-glucosidase. Reduced enzyme activity results in abnormal intra- and extralysosomal glycogen deposition as well as impaired cellular function and autophagy. Age at manifestation and severity of disease depend on residual enzyme activity. Enzyme replacement therapy (ERT) is available since 2006. In infantile onset Pompe disease, the most severe form, markedly prolonged survival has resulted in a new phenotype with symptoms and problems not encountered previously. In addition, it became apparent that antibody formation against the recombinant human enzyme may adversely affect the response to ERT. This review summarizes new knowledge gained in the last years concerning care of pediatric patients with Pompe disease and gives recommendations for diagnostics, treatment, and follow-up.
Keywords: Infantile onset Pompe disease; Late onset Pompe disease; alpha-glucosidase deficiency; enzyme replacement therapy; immunomodulation